ANALISIS ZONA KARAKTER EKOLOGIS DAN ELEMEN PENYUSUN LANDSKAP DI KAWASAN PARIWISATA GEOHERITAGE LEMBAH HARAU KABUPATEN LIMA PULUH KOTA - Muhammad Hamdani; Ernawati ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to analyze the ecological character and elements of the landscape in the Harau Valley Geoheritage tourism area, Lima Puluh Kota Regency. Types of quantitative descriptive research in the form of research with methods or case studies. Data were analyzed using ovaly technique with ArcGIS application and literature study. The results of the study found that the ecological zone in the Harau Valley Geoheritage area is divided into three ecological zones, namely a low ecological zone, a medium ecological zone, and a high ecological zone. The Geoheritage of the Harau Valley is in a zone dominated by a moderate ecological zone, which is 131.48 km2 or as much as 43% of the total area of ​​Harau District, where management in this area must be based on nature conservation to anticipate natural damage/disasters. Based on the results of landscape identification, the constituent elements of the Harau Valley Geoheritage area have natural features such as forests, waterfalls, hills, and cliffs. Meanwhile, the artificial features in the Harau Valley Geoheritage area are settlements, plantations, and agriculture. The character of the landscape in the Harau Valley Geoheritage area is dominated by natural features. Keywords: Geoheritage, Harau Valley, Ecological Zone